2021
DOI: 10.3390/molecules26030539
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of Polycyclic Aromatic Hydrocarbons in Polyhydroxyalkanoates Produced from Mixed Microbial Cultures and Municipal Organic Wastes at Pilot Scale

Abstract: Polyhydroxyalkanoates (PHAs) are well-known biodegradable plastics produced by various bacterial strains, whose major drawback is constituted by the high cost of their synthesis. Producing PHAs from mixed microbial cultures and employing organic wastes as a carbon source allows us to both reduce cost and valorize available renewable resources, such as food waste and sewage sludge. However, different types of pollutants, originally contained in organic matrices, could persist into the final product, thus compro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…These substances can migrate through the technology chain into the final product. Different PHA samples produced using the pilot-scale platform described in Moretto et al [49] were analyzed to quantify relevant contaminants, such as polycyclic aromatic hydrocarbons [175], polychlorinated biphenyls (PCB) [176] and heavy metals [177]. In these PHA samples derived from urban organic waste, the total contents of the three categories of substances complied with the present guidelines and regulations.…”
Section: Market Projections For Bio-plasticsmentioning
confidence: 99%
“…These substances can migrate through the technology chain into the final product. Different PHA samples produced using the pilot-scale platform described in Moretto et al [49] were analyzed to quantify relevant contaminants, such as polycyclic aromatic hydrocarbons [175], polychlorinated biphenyls (PCB) [176] and heavy metals [177]. In these PHA samples derived from urban organic waste, the total contents of the three categories of substances complied with the present guidelines and regulations.…”
Section: Market Projections For Bio-plasticsmentioning
confidence: 99%
“…Secondly, it has been shown that the fermented effluents need some pretreatments (filtration) to ensure that the inhibitory compounds, such as ammonia and excess growth factors, are removed before being used in PHA production [71]. A broad range of microbes (as pure cultures or mixed-microbial cultures) have been used for PHA production [72].…”
Section: Biobased Polymersmentioning
confidence: 99%
“…The results suggest that it can be used directly as a sustainable and effective carbon source with remarkable economic and environmental benefits ( Figure 3 ). Furthermore, the whole set of materials was also analyzed for the determination of relevant contaminants, such as heavy metals [ 46 ], polycyclic aromatic hydrocarbons (PAH) [ 47 ], and polychlorinated biphenyls (PCB) [ 48 ]. The studies demonstrated that all the MMC-PHAs met regulatory standards required for traditional plastic materials.…”
Section: Novel Research and Perspectivesmentioning
confidence: 99%